PEMAKAIAN ADVERBIA TUNGGAL DALAM NOVEL THE SOULS FANTASIA KARYA WINA BOJONEGORO - Rustiati, Rustiati (Widya Warta, 2019)
Adverb is one class of words or categories of words that are quite complicated to know and determine their word identities. Therefore, adverb needs to be studied. Adverb as a word class must be distinguished from information as a function of sentences. The researcher discussed a single adverb in basic form at the phrase level. In the phrase level, a single adverb described verbs, adjectives, nouns, numerals, pronouns, adverbs, conjunctions, prepositions, and particles.This study aims to describe single adverb types in Wina Bojonegoro's The Souls Fantasia novel, its syntactic behavior, and its relational meaning.The results of this study are that: (1) single adverb types have 14 types in 70 forms. The seventy forms described verba, adjectiva, noun, pronoun, numeralia, adverb, conjunctions, prepositions, and particles. (2) Seen from the syntactic behavior, a single adverb had a position on the left and to the right of the word described. Some positions on the left and on the right were strong and some others were not strong. (3) Adverb meanings can be seen from the semantic behavior of 28, namely the meaning of intimacy, beginning, continuity, obsolescence, frequency, certainty, possibility, necessity, qualitative, quantitative, limitation, ability, truth, habit, opposition, denial, prohibition, addition, prejudice and frequency, prejudice and limitation, continuity and qualitative, continuity and limitation, obsolescence and qualitative, certainty and limitation, qualitative and frequency, ability and addition, denial and frequency, prohibition and intimacy.